2022
DOI: 10.3389/fncel.2022.926096
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Dependent Changes of Visual Function and Electrical Response of the Retina in the rd10 Mouse Model

Abstract: One of the critical prerequisites for the successful development of retinal prostheses is understanding the physiological features of retinal ganglion cells (RGCs) in the different stages of retinal degeneration (RD). This study used our custom-made rd10 mice, C57BL/6-Pde6bem1(R560C)Dkl/Korl mutated on the Pde6b gene in C57BL/6J mouse with the CRISPR/Cas9-based gene-editing method. We selected the postnatal day (P) 45, P70, P140, and P238 as representative ages for RD stages. The optomotor response measured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 109 publications
1
8
0
Order By: Relevance
“…Moreover, we explored the morphology and distribution of RGCs via immunostaining Brn-3a, a transcription factor highly specific for RGCs in the retina (Figure 9H,K). Regarding retina architecture during the degeneration process of rd10 mice, it has been described that RGCs do not show significant changes until nine months of age [68]. As expected, we found that PIC-OCT did not induce significant changes in RGCs at P28 compared with the untreated group (Figure 9H,K).…”
Section: Pic-oct Treatment Inhibited the Formation Of Par-polymers An...supporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, we explored the morphology and distribution of RGCs via immunostaining Brn-3a, a transcription factor highly specific for RGCs in the retina (Figure 9H,K). Regarding retina architecture during the degeneration process of rd10 mice, it has been described that RGCs do not show significant changes until nine months of age [68]. As expected, we found that PIC-OCT did not induce significant changes in RGCs at P28 compared with the untreated group (Figure 9H,K).…”
Section: Pic-oct Treatment Inhibited the Formation Of Par-polymers An...supporting
confidence: 82%
“…Notably, a 20% reduction in rod bipolar cells emerges between P45 and P105, and a 39% decrease in horizontal cells is observed between P45 and P270. Intriguingly, RGCs do not exhibit significant changes until the mice reach nine months of postnatal age [68,106]. Exploring the enduring impact of PIC-OCT on rd10 mice through an extended treatment could offer valuable insights, providing a robust confirmation of its effects on RGCs.…”
Section: Discussionmentioning
confidence: 99%
“…The visual signals of the ganglion cells are surprisingly robust, exhibiting small decreases in receptive field size (Figures 7G and 7H) and sensitivity (Figures 7K and 7L) but relatively normal temporal integration (Figures 7I and 7J) and information rates (Figures 7E and 7F). Though ganglion-cell responses in rd10 mice eventually degrade and disappear, 42 our results indicate that most of the mechanisms of visual integration in the outer and inner plexiform layers are intact and continue to function for a prolonged period, providing the mouse-at least under photopic conditions-with substantial visual function.…”
Section: Articlementioning
confidence: 66%
“…To investigate the RGC response range to changing pulse amplitudes, we applied stimulus amplitudes ranging from 1 to 50 ”A with a fixed pulse duration of 500 ”s. Our previous study identified this stimulus range (from 1 to 50 ”A with a fixed pulse duration of 500 ”s) as the optimal parameter to induce RGC spiking in WT and RD mice [10]. In both the normal and RD monkeys, more RGC spikes were elicited with the increasing pulse amplitude.…”
Section: Rd Monkey Retinas Need Higher Threshold Charge Density Thane...mentioning
confidence: 98%
“…Through the progressive disappearance of the photoreceptor, the remaining retinal neurons migrate and form an abnormal synaptic connection [7]. The degenerate retina induces changes in the electrophysiological properties of RGCs, such as the appearance of an abnormal oscillation of the local field potential [8], the correlated firing of spikes among RGCs [9], multiple responses to a single pulse of electrical stimulation [10], and a reduced consistency in electrically evoked network-mediated responses [11]. Thus, an understanding of the RD network is a prerequisite for developing a retinal prosthesis for the blind.…”
Section: Introductionmentioning
confidence: 99%